Comparison of a novel isthmic circumferential suture and Bakri balloon technique for the treatment of uterine atony during cesarean section - Yildirim, Mem Arjen; Kavak, Salih Burcin; Kurkut, Bulent; Sanli, Cengiz; Batmaz, Ibrahim; Bulu, Gulay (Taylor & Francis Ltd, 2022)
Background Postpartum bleeding is a life-threatening obstetric complication. The most common cause is uterine atony. There is no method that can treat PPH with 100% effectiveness and therefore, efforts for the development of more effective conservative treatment methods continue. The aim of the study is to compare the effectiveness of the isthmic circumferential suture technique and the Bakri balloon tamponade in the treatment of postpartum bleeding due to uterine atony during cesarean operation. Methods This study was conducted by retrospectively evaluating the cases who developed uterine atony during cesarean section. Group 1 (n = 15) consisted of the patients who had undergone the isthmic circumferential suture technique, and Group 2 (n = 15) comprised patients who had undergone the Bakri balloon tamponade. The two groups were compared with regard to obstetric characteristics, operative time, preoperative and postoperative features, and neonatal outcomes. Results The groups were similar with regard to age, obstetric characteristics, preoperative complete blood count, neonatal outcomes and there was no statistically significant difference between groups. The operative time was significantly shorter in Group 1 (61.86 +/- 6.7 vs. 69.53 +/- 3.2 min; p < .05). The amount of intraoperative bleeding was lower in Group 1, although there was no statistically significant difference (1793.66 +/- 323.96 versus 1886.33 +/- 343.23 ml; p > .05). The postoperative blood loss was significantly less in Group 1 compared to Group 2 (101.37 +/- 64.6 versus 169.32 +/- 50.0 ml; p < .05). The postoperative 24-hour Htc values were significantly higher in Group 1 (28.83 +/- 2.1 versus 27.08 +/- 2.1 g/dl; p < .05). Conclusion Both methods are effective in the uterine atony during cesarean section. However, due to the shorter operative time and less pre-operative blood loss, the isthmic circumferential suture technique may be a better alternative.
Keywords: Cesarean section; uterine atony; postpartum hemorrhage; isthmic circumferential suture technique; Bakri balloon tamponade